HYGIENIC MONITORING OF WATER BASINS AS SOURCES OF DRINKING WATER (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Water is one of the most essential factors for human health and life. Providing the population with clean and safe drinking water is one of the priority areas of the healthcare system. Therefore, the quality of drinking water sources and their hygienic condition should be constantly monitored.